Piety, politics, and everyday ethics in Southeast Asian Islam : beautiful behavior - Rozehnal, Robert Thomas; Pepinsky, Thomas B., 1979- (London ; New York : Bloomsbury Academic, 2019)
'As an exploration of'beautiful behavior' in theory and practice, this ground-breaking volume explores the incredible diversity and dynamism of Islam in Southeast Asia, both past and present. Amid the dazzling complexity of Islamic civilization, the concept of adab provides Muslims with a shared sense of sacred history, identity, and morality. In the context of Islamic ethics, adab defines the rules of personal and public etiquette: good manners, moral conduct, civility, humaneness, beautiful behavior. Spotlighting the interdisciplinary research of ten prominent scholars, the book offers new perspectives on adab's multiple meanings and myriad applications for Muslim communities in Malaysia and Indonesia. The chapters examine a wide range of texts including the writings of key Muslim thinkers and contexts, focusing on the everyday experiences of lay Muslims. Drawing on a variety of theoretical and methodological lenses, the essays reveal how'beautiful behavior' impacts local institutions, cultural practices, and religious imaginations via politics and law, spirituality and piety, ethics and experience'--
The interplay between adab and local ethics and etiquette in Indonesian and Malaysian literature / Muhammad Ali --'Young people are seeking their blessings' : Islamic life courses, explorative authority, and the possibilities of worldly adab in rural Aceh / Daniel Andrew Birchok -- Adab and the culture of political culture / Thomas Pepinsky -- Sharia, adab and the Malaysian state / Timothy P. Daniels -- Women's adab in the pesantren : gendering virtues and contesting normative behaviors / Nelly van Doorn-Harder -- Politicians, pop preachers, and public scandal : a personal politics of adab / James B. Hoesterey -- Adab and embodiment in the process of performance : Islamic musical arts in Indonesia / Anne K. Rasmussen -- Smoke, fire and rain in Muslim Southeast Asia : environmental ethics in the time of burning / Anna M. Gade.
Includes bibliographical references and index.
Keywords: Islam and culture -- Indonesia; Islam and culture -- Malaysia; Islamic etiquette -- Indonesia; Islamic etiquette -- Malaysia; Islamic ethics -- Indonesia; Islamic ethics -- Malaysia